Economic effects of uncertainty - Michele Piffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This Roundup discusses the literature on the effects of uncertainty on economic activity. Uncertainty will be generally referred to as the agents' inability to form clear expectations about the future path of relevant economic variables. After motivating the analysis from a policy perspective, the Roundup outlines the key channels through which uncertainty exerts an impact on the economy. It then discusses in an intuitive manner the challenges in empirically estimating such effect, and the recent developments in the literature.
Keywords: 330